ANALISIS KEPATUHAN BIDAN DALAM PENERAPAN STANDAR ASUHAN KEBIDANAN: PERAN PENGETAHUAN, SIKAP, PENGAWASAN, DAN REGULASI - Harahap, Nurhayani (Miracle Journal, 2025)
Midwifery care is a crucial element in maternal and neonatal health services aimed at improving the safety of mothers and babies. This study aims to analyze midwives' compliance with midwifery care standards, focusing on factors influencing compliance, such as knowledge, attitudes, supervision, and regulations. This research employs a quantitative approach with a descriptive-analytic design. Data were collected from 100 midwives working in various healthcare facilities in North Sumatra Province through questionnaires, observations, and in-depth interviews. Data analysis was conducted using the Chi-Square test and logistic regression to determine the relationship between these factors and midwives' compliance. The study results show a significant relationship between midwives' knowledge and compliance with midwifery care standards, with a Pearson Chi-Square value of 45.862 and a p-value of 0.000 (p < 0.05). Additionally, midwives' attitudes significantly influenced their compliance with standards, with a Chi-Square test result of 23.853 and a p-value of 0.000. Supervision and regulation also play a crucial role in increasing midwives' compliance, with a Chi-Square value of 45.862 and a p-value of 0.000. Although midwives' knowledge and attitudes were expected to influence compliance, logistic regression analysis showed that supervision and regulations had a more dominant impact than other factors. Midwives' compliance with midwifery care standards is influenced by several key factors, including supervision, regulations, knowledge, and attitudes. To enhance midwives' compliance, strategies such as more intensive supervision, periodic evaluations, and appropriate incentives are necessary. With a comprehensive approach, it is expected that the quality of midwifery services will improve, ultimately contributing to a reduction in maternal and infant mortality rates.